From the streets to the town halls: Municipalist platforms in the post-Yugoslav space. - Milan, Chiara (Urban Studies (Sage Publications, Ltd.), 2023)
In the last decade, urban social movements that emerged in the Yugoslav successor states decided to form political platforms to enter the institutional arena, often after years of mobilisation for the right to the city. Their aim was to seize power at the local level, trying to provide an answer to the crisis of representative democracy and to oppose the process of centralisation of power. These platforms ran for elections in Zagreb (Croatia) and Belgrade (Serbia), to reclaim local autonomy on societal, environmental, economic and political matters. Based on ethnographic work, document analysis and a series of in-depth interviews with activists, this article explores the trajectories of two platforms, 'Zagreb Is Ours' (Zagreb je naš) in Zagreb, Croatia, and 'We Won't Let Belgrade D(r)own' (Ne davimo Beograd) in Belgrade, Serbia. It analyses the factors accounting for the choice of urban activists to embrace new municipalist ideas as strategic ideological and political positioning of their electoral platforms, arguing that the reasons are twofold: the embeddedness into regional and transnational activist networks, which facilitated the process of diffusion of new municipalist ideas across Europe and locally, and the resonance of new municipalism with socialist Yugoslavia's decentralised system of self-management and direct democracy, an historical experience that the platforms' initiators partially reappraised.